A discrimination study of Asia ginseng and America ginseng by a comparison of ginsenosides, oligosaccharides and amino acids using a UPLC-MS method. Issue 13 (27th August 2018) - He, Yang-Fang; Cai, Han-Qing; Li, Wen-Ying; Xiu, Yang; Liu, Wen-Long; Chi, Hong-Yue; Shen, Hong; Yang, Mao-Guang; Pei, Jin; Liu, Shu-Ying
Abstract: A quantitative analysis of ginseng chemical ingredients was established using UPLC-MS, in which the concentrations of ginsenosides, oligosaccharides, and amino acids in ginseng were determined. Unlike the C18 column, which showed good performance in the determination of ginsenosides, the NH2 column was used in this method, and it exhibited good separation abilities for three types of compounds, including 6 saponins, 4 oligosaccharides, and 15 amino acids. For each type of compound, a recovery of 88%–111%, with relative standard deviations (RSD) better than 6% ( n ＝6) were obtained; the limits of quantification (LOQ) for three types of substances were less than 1μg/mL. Furthermore, the method showed strong ability on the discrimination Asia Ginseng and America Ginseng, and was confirmed to be robust, selective, sensitive, rapid and inexpensive.GRAPHICAL ABSTRACT